Analysis of the impact of the productive zakat program on reducing poverty during the pandemic using the CIBEST model in the Banjarnegara district baznas - Ahmad Solikhun Solikhun; Ida Hayu Dwimawanti; Sri Indarti (Jurnal Mantik, 2023)
This study aims to determine the impact of productive zakat funds in reducing poverty. This research uses qualitative research methods, focusing on the Analysis of the Impact of the Productive Zakat Program on Reducing Poverty during the Pandemic Using the CIBEST Model in Baznas, Banjarnegara Regency. The data collection techniques used in this study were data collection techniques by observation, documentation, and in-depth interviews with zakat recipients. The results of this study show that based on analysis using the CIBEST analysis model, productive zakat fund assistance has a positive and significant impact in reducing poverty during the Covid-19 pandemic, both material and spiritual poverty, so that household life must be prosperous. This can be seen in the decrease in material poverty. In contrast, spiritual poverty shows that mustahik recipients of productive zakat funds who initially never performed worship such as prayer, zakat, or fasting, the mustahik turned into obedient to perform worship